Search Direction: Position Externalities and Position Auction Bias - Anderson, Simon P; Renault, Régis (Review of Economic Studies, 2026)
We formulate a tractable model of pricing under directed search with heterogeneous firm demands. Demand characteristics drive bids in a position auction and enable us to bridge insights from the ordered search literature to those in the position auction literature. Equilibrium pricing implies that the marginal consumer’s surplus decreases down the search order, so consumers optimally follow the firms’ position ordering. A firm suffers from “business stealing” by firms that precede it and “search appeal” from subsequent firms. We find rankings that achieve the maximal joint profit or consumer surplus by constructing firm-specific scores. A generalized second price auction for positions endogenizes equilibrium orders and bids are driven by position externalities that impact incremental profit from switching positions. The joint profit maximization order is upheld when firm heterogeneity concerns mostly their mark-up potentials. But the consumer welfare order is robust when firms differ mostly over their potential market sizes.